ANALISIS RESPON SISWA TERHADAP MEDIA ANIMASI POWERPOINT POKOK BAHASAN KALOR - Devi Nanda Efendi; Bambang Supriadi; Lailatul Nuraini (Universitas Jember, 2021)
Online learning is one form of adaptation in the field of education to face of the covid 19 pendemic. Existing technology continues to be developed for both online meeting needs and digital learning media that is suitable to support distance learning systems. One of the lesson that is considered to be lacking in utilizing digital learning media is physics. The purpose of this research was to describe student’s response to the powerpoint animation media of the heat lesson in physics. The research method used as descriptive. The respondents of this research were students of grade XI MIPA 1 SMA Negeri 1 Tanggul consisting of 32 students. This research uses data retrieval techniques through student response questionnaires consisting of aspects of operation/use of media and usage reactions. The results of the students’ response analysis to the use of powerpoint animation media amounted to 81,33% with details on each aspect was 81,41% on the aspect of media use and by 81,25% on the aspect of usage reaction. Based on the results of the research that has been done, it can be stated that the powerpoint animation media of the subject of heat received a very positive response from the respondents.